A writer’s reference - Hacker, Diana (Bedford/St. Martin’s, 2009)
A Writer’s Reference is the most widely adopted college handbook ever published. The new edition is available in a classic version that provides more help with academic writing, serves a wider range of multilingual students, and lends more support for college research — all in an easy-to-use quick-reference format.